Essays on regional economic development and innovation ecosystems in the arctic context - Niemelä, Sami (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2018)
This dissertation consists of introductory part and four essays each covering certain aspects to regional development. Three of the essays are research reports from joint and multi-disciplinary research efforts. The main driver for research activities has been to deepen the understanding of regional development in the modern context dominated by phenomena such as urbanization.When the natural and even decades ago forecasted mobility of economic activities seems to be towards central, metropolitan areas and whenmetropolitan cities produce themajority of national GDP, the concern about differences in regional development becomes justified. As well as urbanization has prompted research projects, the second important issue has been to analyze the need for regional policy. Therefore, it has been studied whether there are – besides pure political reasons – any grounds for active regional policy programs. The three research reports included in this dissertation are built in case study fashion on the Arctic region – the Scandinavian Arctic, to be precise. The Arctic has been presented as an area, which is struggling with typical challenges of periphery but also as an area of special economic interest due to natural resources as well as experiments in innovation activities. Moreover, since digitalization is unanimously identified, alongside with urbanization, as another mega trend it is reasonable to inspect peripheral communities and their functions from the perspective of rapidly developing technologies, which presumably fade out the importance of geographical locations. The fourth essay in this dissertation deepens the economic approach to the concepts of innovations and technological change. The general outline of the research consists of three elements. First, the concept of an innovation ecosystem is considered as a platform for regional development. Secondly, the case area is studied to understand the potential need for and requirements to corresponding regional development policy. The second element contains also a study on the economic potential of the case area. Finally, the concept of regional policy is expanded over national boundaries and opportunities for multi-national collaboration are studied. The research results show that reorganizing local development activities indeed requires a new kind of role for public sector. Oulu Innovation Alliance was investigated as a regional concept and concluded to contain various elements of an innovation ecosystem. Moreover, it is argued that the challenges of Arctic context are efficiently met when public sector adopts a role of an enabler and networker. Studying Arctic innovation systems and their effect on the regional economies can offer new insights to the challenges of other peripheral regions as well.

Tämä väitöskirja koostuu johdanto-osasto ja neljästä esseestä, joista jokainen liittyy alueelliseen kehittymiseen. Esseistä kolme on tutkimusraportteja monitieteellisestä tutkimustyöstä, jonka tavoitteena on ollut syventää näkökulmaa aluekehitykseen modernissa toimintaympäristössä, jossa vallitsevina trendeinä ovat kaupungistumisen kaltaiset ilmiöt. Taloudellisen toiminnan keskittyminen metropolialueille on taloustieteen kannalta monin tavoin luonnollinen ja ennustettukin kehityssuunta, mikä osaltaan korostaa aluetaloudellisen tarkastelun tarpeellisuutta. Toinen tutkimustyötä ohjannut tavoite on ollut analysoida aluepolitiikan tarvetta, joten tutkimuksen avulla on selvitetty perusteita erilaisille aluekehitysohjelmille. Väitöskirjaan sisältyvissä tutkimusraporteissa tarkastellaan Skandinavian arktisia alueita aluekehityksen esimerkkeinä. Arktiset alueet ovat tyypillisiä perifeerisiä alueita,mutta toisaalta alueen luonnonvarat ja pohjoisen alueen innovaatiokokeilut ovat lisänneet kiinnostusta alueiden kehittämiseen. Nopeasti etenevän digitalisaation ja teknologisen muutoksen odotetaan häivyttävän eri toimintojen maantieteellisen sijainnin merkitystä, mikä osaltaan vahvistaa tarvetta tutkia myös syrjäisten alueiden toimijoita ja toimintoja. Tämän väitöskirjan neljäs essee syventää innovaatiotoimintaan ja teknologiseen muutoksen liittyvää taloustieteellistä tarkastelua. Tässä väitöskirjassa esitettävän tutkimuskokonaisuuden voidaan kuvata koostuvan kolmesta elementistä. Ensimmäisenä elementtinä on innovaatioekosysteemi aluekehityksen alustana. Toisena elementtinä kokonaisuudessa on esimerkkialueen tutkiminen sekä aluekehityksen ja -politiikan että taloudellisten mahdollisuuksien näkökulmista. Tutkimustoiminnan kolmantena elementtinä on aluepolitiikan käsitteen laajentaminen yli maiden rajojen tapahtuvaksi yhteistyöksi ja tällaisen yhteistyön mahdollisuuksien arviointi esimerkkialueella. Tutkimustulokset osoittavat, että alueellisen kehittämistoiminnan uudelleen organisointi edellyttää julkisen sektorin roolin uudistamista. Tutkimuksen kohteena olleen alueellisen ratkaisun, Oulun innovaatioallianssin, todettiin sisältävän useita innovaatioekosysteemin piirteitä. Lisäksi voitiin todeta, että julkisen sektorin toiminnan muokkaaminen muiden sektoreiden toimintaa mahdollistavaksi verkostotoimijaksi on tehokas tapa vastata arktisen toimintaympäristön haasteisiin. Arktisten innovaatiojärjestelmien tutkiminen ja arvioiminen voi tuottaa uusia näkökulmia muidenkin perifeeristen alueiden ongelmiin.